RESPON PERTUMBUHAN PROTOKORM ANGGREK SENDU (Grammatophyllum stapeliiflorum) DENGAN PENAMBAHAN BEBERAPA JENIS PUPUK DAUN SECARA IN VITRO - Isda, Mayta Novaliza; Wusqa, Wasila (Jurnal Agroteknologi, 2024)
Indonesia has 26,000 species of orchids that are very potential and profitable. Grammatophllum stapeliiflorum is an orchid species that is increasingly difficult to find in its natural habitat. The addition of foliar fertilizer containing macro and micro nutrients can increase plant growth. The purpose of this study was to determine the effect of foliar fertilizer type, concentration and the combination of the two factors on the growth of the orchid protocorm G. stapeliiflorum. This study used a factorial completely randomized design with two research factors, namely the type of foliar fertilizer with 2 treatment levels, B1 = Gandasil-D and B2 = Growmore. The second factor, fertilizer concentration with 4 treatment levels, namely A0 = control (without foliar fertilizer), A1 = 1 g/L, A2 = 2 g/L, and A3 = 3 g/L. This study consisted of 8 treatment combinations which were repeated 4 times, resulting in 32 experimental units. The parameters observed were the percentage of live explants, the percentage of browning, and the percentage of protocorms growth stages. Data were analyzed by Analysis of Variance (ANOVA) and continued with Duncan's Multiple Range Test (DMRT) at a 5% level. These results indicated that the application of foliar fertilizers with Gandasil-D and Growmore affects the percentage of live explants and protocorm growth phases and also increase the percentage browning until of 32,5%. Gandasil-D is better for protocorm growth from globular to torpedo. The control is better for forming shoot of 22,5% compared to the use of foliar fertilizer.